2004
DOI: 10.1002/col.10231
|View full text |Cite
|
Sign up to set email alerts
|

Museum lighting: Optimizing the illuminant

Abstract: Museums must choose illumination that will optimize observers' aesthetic experiences without compromis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 11 publications
(10 reference statements)
2
34
0
Order By: Relevance
“…Furthermore, the appearance of blues are often more sensitive to lighting properties than other colors. 22 Including this range of blues is a significant difference when compared with research using printed reproductions 5,6,12,14 in which phthalocyanine blue is used exclusively, a pigment that is fairly robust to changes in lighting.…”
Section: Artist Materials Datasetmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, the appearance of blues are often more sensitive to lighting properties than other colors. 22 Including this range of blues is a significant difference when compared with research using printed reproductions 5,6,12,14 in which phthalocyanine blue is used exclusively, a pigment that is fairly robust to changes in lighting.…”
Section: Artist Materials Datasetmentioning
confidence: 98%
“…Advances in reflector properties have led to incandescent tungstenhalogen multifaceted reflector (MR) lamps that can achieve CCTs of 5000 K. 4 Thus, it is possible to use conventional spot illumination with a range of CCTs. Scuello et al 5,6 performed visual experiments evaluating printed reproductions of artwork; they found that observers preferred a CCT of 3600 K for lighting ranging between 2500 and 7000 K at an illuminance of 200 lx. The dominant lighting for the display of art remains natural daylight and incandescent.…”
Section: Introductionmentioning
confidence: 99%
“…Based on these facts one might conclude that, for museum lighting, one should select a light source with not too high a CCT, e.g. 3000 K to 3500 K and low illumination (Scuello et al came to the conclusion that observers preferred 3600 K and 200 lx for a mock-up museum gallery with post-card size images 17 ), and try to use a SPD that will provide a colour perception for the pigments under these conditions as would be the case under daylight and much higher illumination, i.e. one should base the calculation on a proper chromatic adaptation transformation.…”
Section: The Reference Illuminantmentioning
confidence: 99%
“…Empirical studies have shown that observers prefer daylight illumination with specific correlated colour temperatures (CCT) to render artistic paintings (Scuello et al. , 2004; Pinto et al.…”
Section: Introductionmentioning
confidence: 99%